Efeitos farmacológicos, fenotípicos e proteômicos do tratamento com PTC (+) em linhagens de câncer de próstata - Farias, Kaio Moraes de (2017)
Malignant neoplasms are increasing with the progressive control of other diseases and consequent aging of the population. The search for anticancer agents is still necessary since the drugs available so far are not enough to control the disease. In addition, many drugs have quite pronounced side effects or the cells develop resistance, which limits a therapy. Pterocarpans (PTC) represent the major class of isoflavonoids after isoflavones and studies show activities such as: antifungal, antibacterial, insecticidal and antitumor. The present study evaluated the antiproliferative effect of PTC (+) on prostate cancer cell lines, most prominently for a PC3 cell line. A pharmacological, phenotypic and proteomic approach was used. The results showed a potential anti-cancer activity that the PTC (+) caused against prostate cell lines, causing cell cycle arrest in (G2/M) in prometaphase, decreasing cell proliferation. The arrangement of mitotic spindles in monopoles, for the most part, was present in 2.5 μM and 7.95 μM treatments. The treatment with PTC (+) caused disorganization of the centrosomes, compromising their integrity; however, the treatment did not prevent the division of the centrioles. Furthermore, after a long period of exposure to PTC, the actin network was compromised by fiber disorganization and polarization in cortical regions and at focal points in the cellular cytoplasm. The treatment with PTC (+) modified the PC3 proteome. Differentially expressed proteins were analyzed in terms of their biological processes, molecular function, cellular component, pathways and class of protein. Proteins associated with cytoskeletal processes, folding/unfolding, actin network and cell division were, for the most part, negatively regulated in the treatment. Interestingly, a CH3 (downregulated) gene`s protein is identified as a potential trigger for all observed phenotypic effects. The PTC (+) results presented suggest that its mechanism of action involves more than one target, making it a model in the research and development of multi-target compounds and multi-segmented action.